2015
DOI: 10.4238/2015.march.27.13
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, partial characterization, and cloning of an extracellular chitinase from the entomopathogenic fungus Verticillium lecanii

Abstract: ABSTRACT. The entomopathogenic fungus Verticillium lecanii is a well-known biocontrol agent of fungal phytopathogens, as well as insect pests. A 42-kDa chitinase belonging to family 18 of the glycosyl hydrolases was isolated and partially characterized. Chitinase was purified using successive column chromatography on phenyl-sepharose, DEAE-sepharose, and CM-sepharose. The enzyme showed the highest activity at 40°C and pH 4.6. Enzyme activity was strongly activated in the presence of Mg 2+. The purified enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Our resuls showed that chitinase PeChi68 showed various inhibitory activities against conidial germination depending on the species of fungus, in aggrement with previous findings showing that bacterial and fungal chitinases have various inhibitory activities against spore germination depending on the source of spores (Banani et al, 2015; Broadway et al, 1995; Di Maro et al, 2010; Frankowski et al, 2001; Harman et al, 1993; Kamensky et al, 2003; Yu et al, 2015). It has been reported that one chitinase produced by a yeast can completely inhibit conidial germination of Monilinia spp., a post-harvest pathogen causing of brown rot of stone fruits (Banani et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Our resuls showed that chitinase PeChi68 showed various inhibitory activities against conidial germination depending on the species of fungus, in aggrement with previous findings showing that bacterial and fungal chitinases have various inhibitory activities against spore germination depending on the source of spores (Banani et al, 2015; Broadway et al, 1995; Di Maro et al, 2010; Frankowski et al, 2001; Harman et al, 1993; Kamensky et al, 2003; Yu et al, 2015). It has been reported that one chitinase produced by a yeast can completely inhibit conidial germination of Monilinia spp., a post-harvest pathogen causing of brown rot of stone fruits (Banani et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Usually, EPFs particularly L. lecanii produces extracellular pathogenesis-related proteins or insecticidal metabolites such as cyclodepsipeptide (bassianolide), chitinases, etc. [14,32,33]. In our study, L. lecanii-derived proteins would most probably be chitinases corresponding to 44 and 33 kDa [33,34].…”
Section: Discussionmentioning
confidence: 51%
“…[14,32,33]. In our study, L. lecanii-derived proteins would most probably be chitinases corresponding to 44 and 33 kDa [33,34]. Compared to buffertreated control plants, cotton plants treated exogenously by the foliar application of L. lecanii protein exhibited considerable reduction of fecundity rate of B. tabaci.…”
Section: Discussionmentioning
confidence: 54%
“…Fungal chitinases play key roles in nutrition, morphogenesis, autolysis, competition, defense, or parasitism. Mycoparasitic, nematophagous [ 48 ], and entomopathogenic fungi [ 9 , 31 , 49 ] have been reported to produce chitinolytic enzymes that contribute to their biocontrol potentials. The functions and biocontrol potential of chitinases are widely known and well-reviewed [ 50–52 ].…”
Section: Diversity Of Roles In Naturementioning
confidence: 99%